answersLogoWhite

0


Best Answer

6+7a+6b

User Avatar

Wiki User

โˆ™ 2009-10-21 14:30:29
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: Simplify 2a plus 3b plus 5a plus 6 plus 3b?
Write your answer...
Submit
Related questions

How do you simplify 2a plus 5a?

Add them together: 2a+5a = 7a


Simplify 5a-3b plus 9c?

-6(a-3b-9c)


What is -5a plus 2b plus 3a plus b?

-2a plus 3b


Simplify 3aยฒ plus a-aยฒ plus 5a?

2a² + 6a


How do you simplify 2a plus 10 plus 5a-2?

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8


Simplify 2a plus 11a minus 5a?

2a + 11a - 5a = 8a


5a squared plus 3b squared plus 2a squared plus 4b squared?

No


What is 2a plus 3b?

2a + 3b


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


5a 2 plus 3b 2 plus 2a 2 plus 4b 2?

20a2b2


Simplify 3a plus 5 plus 2a plus 6?

5a + 11


Simplify 5aยณ - 4ab plus 2aยณ as much as possible?

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.


What is 16a plus 3b-c-5a plus 3b plus 7c plus a equals?

12a + 6b + 6c = 6(2a + b + c)


What is 7a plus 3b minus 5a minus 2b minus b?

2a


Simplify 9a plus 8 minus 2a minus 3 minus 5a?

2a+5


Simplify 2a plus 3a plus 4 equals?

2a + 3a + 4 = 5a + 4


2a plus 5a plus 9a equals?

2a+5a+9a = 16a


What does 2a plus 5a plus 3a equal?

2a + 5a + 3a = 10a


What is 3a plus 2b plus 3c plus 2a plus 4c plus b equals?

Gathering like terms together, this is equal to 5a + 3b + 7c.


Simplify 3a4-2a2 plus 5a-10 - 2a4 plus 4a2 plus 5a-2 equals?

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)


What is 9a plus 8-2a-3-5a?

9a +8 -2a -3 -5a = 2a +5


5a plus 2a 6-6a?

The value of a in the equation 5a plus 2a = 6-6a is a=6/11.


What is 5a plus 3 plus 2a-2 plus a?

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1


What is 5a - 4b plus 2c - 3b - 6c plus a?

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].


What is 2a plus 3a?

2a + 3a = 5a